«E-Learning» technology and its application by the teaching of the Korean language in Kazakhstan (Journal of Oriental Studies, 2016)
The article about the using of E-Learning technology in the teaching of the Korean Language.There are the most popular educational sites and their characteristics which suitable for audience of Kazakhstan’s university. Thereby any students take a good opportunity to learn the Korean language in the conditions which are close to the language environment.
Keywords: e-learning (e-learning); ICT (information and communication technologies); distance learning